2021
DOI: 10.1371/journal.pone.0247052
|View full text |Cite
|
Sign up to set email alerts
|

Libman-Sacks endocarditis and associated cerebrovascular disease: The role of medical therapy

Abstract: Background Libman-Sacks endocarditis in patients with systemic lupus erythematosus (SLE) is commonly complicated with embolic cerebrovascular disease (CVD) or valve dysfunction for which high-risk valve surgery is frequently performed. However, the role of medical therapy alone for Libman-Sacks endocarditis and associated acute CVD remains undefined. Objective To determine in this cross-sectional and longitudinal study if conventional anti-inflammatory and anti-thrombotic therapy may be an effective therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Other investigations, however, have reported that patients with SLE may have a threefold to fivefold increased in surgical morbidity and mortality 24 25. Moreover, conventional anti-inflammatory and antithrombotic therapy may obviate the need for high-risk valvular surgery 26. Despite this, many patients in our cohort were poor surgical candidates due to advanced age and comorbid conditions.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Other investigations, however, have reported that patients with SLE may have a threefold to fivefold increased in surgical morbidity and mortality 24 25. Moreover, conventional anti-inflammatory and antithrombotic therapy may obviate the need for high-risk valvular surgery 26. Despite this, many patients in our cohort were poor surgical candidates due to advanced age and comorbid conditions.…”
Section: Discussionmentioning
confidence: 77%
“…24 25 Moreover, conventional anti-inflammatory and antithrombotic therapy may obviate the need for high-risk valvular surgery. 26 Despite this, many patients in our cohort were poor surgical candidates due to advanced age and comorbid conditions. Only three (6.3%) patients underwent cardiac surgery; one of them died shortly after intervention and the others had no postoperative complications.…”
Section: Valvular Heart Diseasementioning
confidence: 94%
“…In a recent longitudinal and cross-sectional study, patients with SLE and Libman-Sacks endocarditis complicated by embolic cerebrovascular disease were treated with conventional anti-inflammatory and anti-thrombotic therapy for six months; on the follow-up TEE, 76% of the patients experienced resolved or improved valvular vegetation or regurgitation. 22 In another six-year longitudinal and cross-sectional study, 16% of patients had new or recurrent stroke, 14% had cognitive disability, and 9% died. 16 …”
Section: Discussionmentioning
confidence: 97%
“…Management of LSE and the usefulness of immunosuppressive for valvular regurgitation were not described in detail before in the pediatric age group but some evidence in the adult population [ 8 , 12 - 13 ]. For instance, Ishizu et al [ 10 ] reported a dramatic improvement after using immunosuppressive medication in LSE with severe mitral regurgitation.…”
Section: Discussionmentioning
confidence: 99%